Continuous microfluidic mixing and the highly controlled nanoparticle synthesis using direct current-induced thermal buoyancy convection - Zhang, Kailiang; Ren, Yukun; Hou, Likai; Tao, Ye; Liu, Weiyu; Jiang, Tianyi; Jiang, Hongyuan (Microfluidics and nanofluidics, 2020)
We present a flexible and noninvasive approach for efficient continuous micromixing and microreaction based on direct current-induced thermal buoyancy convection in a single microfluidic unit. Theoretically, microfluids in this microsystem are unevenly heated by powering the asymmetrically arranged microheater. The thermal buoyancy convection is then formed to induce microvortices that cause effective fluidic interface disturbance, thereby promoting the diffusion and convective mass transfer. The temperature distribution and the convection flow in the microchip are first characterized and studied, which can be flexibly adjusted by changing the DC voltage. Then the mixing performance of the presented method is validated by joint numerical and experimental analyses. Specifically, at U = 7 V, the mixing efficiencies are higher than 90% as the flow rate is lower than Q v = 600 nL/s. So high-quality chemical or biochemical reactions needing both suitable heating and efficient mixing can be achieved using this method. Finally, as one example, we use this method to synthesize nano-sized cuprous oxide (Cu 2 O) particles by effectively mixing the Benedict’s solution and glucose buffer. Remarkably, the particle size can be tuned by changing the voltage and the concentration of Benedict’s solution. Therefore, this micromixer can be attractive for diverse applications needing homogeneous sample mixtures.